“Ogre” Reflection of Belief about Ghosts in Thai Lue Ethnic and Isan Ethnic - Duangmala, Veerachat; Numtong, Kanokporn (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This study aims to compare reflections on ogres in Thai Lue ethnic and Isan ethnic by studying documents and research related to ghosts in Thailand and China. The study is divided into 3 points, including belief about the origin of Ogres in Thai Lue ethnic and Isan ethnic, the process of becoming an Ogre and driving them out Ogres in Thai Lue ethic and Isan ethic, and the interpretation of changes in beliefs about Ogres in modern society. The result of the study found that the belief about the origin of Ogres can be divided into three categories as follows: 1) the history of Ogre, 2) the process of becoming an Ogre, and 3) the cognition of being an Ogre. Furthermore, the process of becoming an Ogre follows 3 distinct stages: Firstly, a person is identified as an Ogre, then a ritual is performed to confirm and banish the Ogre. Finally, the person receives punishment from the society. Two factors were found to contribute to the changing beliefs about Ogres in contemporary society. The utilization of humorous or fantastical films has significantly changed the beliefs about Ogres. Also, diseases have contributed to the change of ancient beliefs about Ogres in modern society.